THE EFFECT OF JOB SATISFACTION AND SCHOOL ORGANIZATIONAL CULTURE ON TEACHER WORK ENCOURAGEMENT AT STATE VOCATIONAL HIGH SCHOOL 3 BOYOLANGU TULUNGAGUNG - Sawal Sartono; Ina Amalia (BEMJ : Business, Entrepreneurship, and Management Journal, 2024)
Morale is the desire to do work more actively, so that the work will be expected to be better. Teacher morale is influenced by several factors, including job satisfaction and school culture. This study aims to determine and examine between theory and reality, that job satisfaction and a good school organisational culture have a positive effect on morale. The objects in this study are Job Satisfaction, School Organisation Culture and Teacher Morale at SMK Negeri 3 Boyolangu. The research location is at SMK Negeri 3 Boyolangu Tulungagung which is located at Jl. Ki Mangun Sarkoro, Beji Village, Boyolangu District, Tulungagung Regency. In this study the method used is quantitative method. Data collection techniques in the study include: interviews, documentation, observation and questionnaires. The data analysis technique uses descriptive percentage analysis and multiple linear regression analysis. The independent variables in this study are job satisfaction (X1) and school organisational culture (X2) while the dependent variable is teacher morale (Y). The results of the study concluded: (1) Teachers' job satisfaction is in high criteria, as well as school organisational culture in good criteria, and teacher morale in high criteria. (2) There is an effect of job satisfaction on teacher morale by 26.52%. (3) There is an effect of school organisational culture on teacher morale by 8.06%. (4) There is an effect of job satisfaction and school organisational culture together on teacher morale with a contribution of 41.6% and the remaining 58.4% is influenced by other factors not examined in this study.